The Effect of the PAIKEM Strategy on Students' Learning Outcomes in Fiqh Thaharah at MTs Nurul Iman Tanjung Morawa - Agustini (Sufiya Journal of Islamic Studies, 2023)
This study examined the effect of the Active, Innovative, Creative, Effective, and Enjoyable Learning (PAIKEM) strategy on students' learning outcomes in Fiqh Thaharah at MTs Nurul Iman Tanjung Morawa. The study used a quantitative field-research approach with a one-group pretest–posttest design involving 60 students. Data were gathered through observation, tests, and supporting documentation, while the learning intervention emphasized student-centered discussion, participation, and contextual engagement with purification material. The findings show that students' post-intervention achievement was high, with 87.5% of students classified in the “very good” category and a mean score of 84.6. The statistical analysis also indicated that the data met the normality and homogeneity assumptions, and the hypothesis test showed a significant effect of the PAIKEM strategy on learning outcomes (t = 2.81 > 1.67). These results suggest that PAIKEM contributes positively to Fiqh learning because it increases participation, reduces monotony, and supports meaningful understanding of practical religious material. The study concludes that PAIKEM is a relevant instructional strategy for Fiqh Thaharah learning in madrasah settings, although its effectiveness should be supported by teacher readiness, instructional media, and a conducive learning environment.